LIMBAH SPREI HOTEL SEBAGAI PRODUK MERCHANDISE DENGAN TEKNIK UPCYCLING - Andrianto, Naomi Eunike Erasti; Laba, I Nyoman; Artayani, Ida Ayu Gede (Pusat Penerbitan LPPM ISI Bali, 2025)
The rapid growth of Bali’s tourism sector has increased hotel occupancy and the frequency of bedsheet replacement, shortening the lifespan of linens and generating large amounts of textile waste. This waste is usually sold without processing, although used hotel linens have high potential as an environmentally friendly and economically valuable upcycling material. This study identifies the potential of hotel linen waste as a recyclable material and describes the process of turning it into value-added merchandise products. The research used a descriptive–collaborative method with a qualitative approach through direct field observation and a review of relevant literature. PT TRI Cinta Bumi, a creative industry engaged in sustainability, was involved to demonstrate how hotel linen waste can be transformed into merchandise. Processing stages included sorting fabrics by quality and color, designing to meet market trends, re-dyeing to enhance visual appeal, and sewing into prototypes. The products were then assessed for aesthetics and functionality and tested with limited market responses to determine acceptance. Findings show that upcycling techniques applied to retired hotel bedsheets produce functional, aesthetically appealing products well received by the market, such as bandanas, small bags, and scrunchies. These results indicate that using textile waste as an alternative raw material offers significant potential to support sustainable practices, design innovation, creative economic empowerment, and market expansion. Furthermore, the process provides new insights for the creative industry on the use of textile waste not only for merchandise but also for decorative items, experimental textile media, and collectible artworks.